PERSEPSI MAHASISWA AKUNTANSI TERHADAP AKUNTANSI SYARIAH: SURVEY PADA PERGURUAN TINGGI UMUM DAN PERGURUAN TINGGI ISLAM DI YOGYAKARTA - , NYAYU SELVIANA WATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to describe the perception of accounting students towards the objectives, characteristics, and userâs degree of interest on shariah accounting. Data collected by distributing questionnaries to universities(islamic and conventional background). The data analytical methods used in this research are chi square test, one sample t-test, cross-tab chi square and Mann Whitney. The results of the statistic test indicates that accounting university students have understood the objectives, characteristics, and userâs degree of interest on shariah accounting is different between conventional accounting. In addition, there are no difference in perception between accounting students who have been/are being taken study in Islamic accounting and accounting students who havenât taken an accounting class to the objectives of shariah accounting. But, there is a difference in perception between this two groups of students to the characteristics and userâs degree of interest on shariah accounting. Keywords : Perception, accounting students, shariah accounting